PENGARUH PENGETAHUAN KEWIRAUSAHAAN DAN KARAKTERISTIK INDIVIDU TERHADAP KEBERLANGSUNGAN USAHA WARUNG AYAM PENYET DI KECAMATAN MEDAN TIMUR - IKA PUSPA SATRIANNY; NICOLAS . (LP2MTBM MAKARIOZ, 2020)
The city of Medan is one of the cities known for its culinary. One of the famous culinarys in Medan City today is the Chicken Distillery, where this one culinary is widely found throughout the Subdistricts in the Medan Region, especially in the Eastern Field Subdistrict. In the East Field Subdistrict, there are 70 units of chicken-breeding in the East Field Subdistrict, of which 70 units have closed 10 units, where there are now 60 units of chicken-breeding in the East Field Subdistrict, as a result of which over the last 3 years the number of consumers tends to decline. This study aims to find out how the influence of the entrepreneurial knowledge of the Poultry entrepreneurs in the East Field Subdistrict and the individual characteristics of the Chicken farmers in the East Field Subdistrict on the continuation of the Chicken's efforts in the East Field Subdistrict. The total population in this study amounted to 60 businessmen in the east field, where the sample-taking technique used a saturated sample technique with a sample of 60 businessmen.The results of the research can be concluded that in a simultant and partially variable knowledge of the heroism of the Poultry entrepreneurs in the East Field Subdistrict and the individual characteristics belonging to the Poultry entrepreneurs in the Eastern Field Subdistrict have a significant influence on the survival of the Chicken effort in the East Field Subdistrict